O jornal comunitário como instrumento de reconhecimento social - Costa, Moema Novais [UNESP]; Rodrigues, Daniela Arcanjo [UNESP]; Aranha, Angelo Sottovia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The university extension project Voz do Nicéia it is connected to the Architecture, Arts and Communication College of Estadual University of São Paulo and it is funded by the Pro-Rectory of University Extension. The project is divided in four work areas: printed newspaper, digital media, events promotion and research group. The Voz do Nicéia seeks to promote the social recognition of Jardim Nicéia population. The neighborhood is a low income district of Bauru, São Paulo. For this, the students of Social Communication: Journalism fully produce a community newspaper that circulate in the area and in the government offices of the city. The population can be considered a real community: the residents face the same problems for being in a limited geographical area and, for that, it is very important the existence of a community newspaper in the area. The Voz do Nicéia is accepted in the community and the participation of the dwellers is valued, because the reports are based in what they think it is important for the district. The project counts with 35 volunteers student-reporters, two scolarships students that are responsible for the coordination of the project and a guide professor.

O projeto de extensão universitária Voz do Nicéia conta com o apoio da Faculdade de Arquitetura, Artes e Comunicação, da Universidade Estadual Paulista (Unesp), e da Pró-reitoria de Extensão Universitária. Compõe-se de quatro atividades articuladas: jornal comunitário impresso, meios digitais, seção de eventos e grupo de pesquisa. Com o Voz do Nicéia o objetivo é promover o reconhecimento social da população do Jardim Nicéia, bairro de baixa renda da cidade de Bauru, São Paulo. Para isso, os estudantes de Jornalismo produzem, integralmente, o jornal comunitário que circula no bairro e em repartições públicas da cidade. O bairro pode ser considerado, de fato, uma comunidade; os moradores enfrentam os mesmos problemas por compartilharem um território geográfico bem definido e limitado, o que legitima a existência de um jornal comunitário na área. O Voz do Nicéia é bem aceito pela comunidade e a participação dos moradores é valorizada, já que as pautas são baseadas no que eles consideram importante para o bairro. O projeto conta com 35 estudantes-repórteres voluntários, duas estudantes bolsistas que organizam as quatro atividades e um professor coordenador.
Keywords: Humans rights; Social recognition; Urban space; Direitos humanos|Reconhecimento social; Espaço urbano